INCREASING NEW ENTREPRENEURIAL INNOVATION IN PASTRY CAKE MAKING ACTIVITIES IN SMALL AND OTHER INDUSTRIES IN WEST JAVA - Utami, Nisa Rahmaniyah (LPPM Univ. Ibn Khaldun Bogor, 2024)
The West Java government is actively improving entrepreneurial skills, especially in the field of pastry in entrepreneurship. One possibility is to train entrepreneurs (MSMEs in the pastry sector) in the tourism sector in the West Java region. This activity is supported by the Ministry of Industry, Directorate General of West Java's small and medium-sized and miscellaneous industries, which is holding this training activity with the aim of increasing new entrepreneurial innovation in pastry making activities in small and other industries in West Java. This activity will last for 3 days in Green Forest Bogor. The training participants consisted of 36 people who work in the culinary industry such as cafes, hotels, restaurants, MSMEs, pastries and resorts in the Bogor area. The method for implementing this activity is through creativity and innovation training with MSMEs and community participation in the culinary sector, especially in the pastry sector.